Financing clean energy projects: New empirical evidence from major investment countries. (May 2021) - Raghutla, Chandrashekar; Shahbaz, Muhammad; Chittedi, Krishna Reddy; Jiao, Zhilun
Abstract: Globally, all countries are worried about rising carbon emissions (greenhouse gas emissions), it leads environmental degradation, increase sea level and reduce agriculture output due to large use of traditional energy resource. As a result, international organizations have begun to pressurize countries to reduce their carbon emissions by increasing the use of clean energy sources. In such circumstances, this study examines the extent to which foreign direct investment (FDI) inflows, stock market capitalization, and research & development expenditures affect clean energy demand in the major investment countries, spanning the period from 1996 to 2017. The empirical results of long-run elasticities show that FDI inflows and research & development expenditures play a considerable role in promoting clean energy consumption. Further, it is indicated that clean energy consumption has a negative effect on carbon emissions, but a positive effect on economic growth. Research & development expenditures and FDI inflows, meanwhile, have a significant negative impact on CO2 emissions. Based on the results, the study recommends that policy makers in the major investment countries should understand that it is worth investing research & development expenditures as it is encouraging the use of clean energy and supporting lower carbon emissions. These empirical findings offer increased understanding for policy makers, enabling them to utilize research & development expenditures as a tool in the energy sector for the improvement of environmental quality. Highlights: We test stock market capitalization and FDI inflows in major investment countries. We apply panel cointegration test and a fully modified OLS approach. FDI inflows and R&D expenditures positively affect clean energy consumption. The study offers increased understanding in the energy sector for policy makers.